A review of Paroplitis (Braconidae, Microgastrinae), and description of a new genus from New Zealand, Shireplitis, with convergent morphological traits - Fernández-Triana, J.; Ward, D. F.; Cardinal, S.; Achterberg, C. Van (Zootaxa, 2013)
A new genus of Microgastrinae, Shireplitis Fernández-Triana and Ward, is described as endemic from New Zealand. Shireplitis resembles the Holarctic genus Paroplitis Mason, although morphological and molecular data reveal they are not likely to be closely related but are an example of convergent evolution. Shireplitis comprises species mostly found in moss, litter, or tussock grasslands, usually at moderate altitude on several New Zealand mountain ranges. Keys to all species from both genera are provided. Seven new species are described: Paroplitis vietnamensis van Achterberg and Fernández-Triana, and six Shireplitis species authored by Fernández-Triana and Ward: S. bilboi, S. frodoi, S. meriadoci, S. peregrini, S. samwisei and S. tolkieni.